Unpacking the Factors that Contribute to Plagiarism Activity among EFL University Students - Syam, Ferawaty; Resyadi, Herman (Universitas Terbuka, 2023)
The research aimed to unpack plagiarism activity among EFL university students. Using a survey method, the data were collected from 60 EFL university students from different institution. The survey focused on students’ understanding on plagiarism, their attitude, and also their experience on plagiarism activity. The research found that majority of students reporting having committed plagiarism on their academic activity. There are factors contributing to plagiarism include a lack of understanding of the material, time limits, and a desire for higher grades. However, the majority of respondents believe that educating students about plagiarism is the most effective strategy in preventing plagiarism, followed by the use of plagiarism prevention tools. Keywords: Plagiarism, EFL students, Survey, Students’ understanding